The Influence of Rewards, Organizational Culture and Work Motivation on Employee Performance - Hamdani, Syaiful Fadhilah; Ali, Hapzi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The Influence of Rewards, Organizational Culture and Work Motivation on Employee Performance is a scientific article on literature studies within the scope of the field of Human Resources Management. The purpose of this article is to formulate a hypothesis regarding the relationship between variables that will be the focus of future research. Research data and information will be obtained from sources on online platforms such as Google Scholar, Mendeley, and other online academic sources. The research method used is library research sourced from e-books and open access electronic journals. Qualitative descriptive analysis. The results of this article: 1) Awards influence employee performance; 2) Organizational culture influences employee performance; and 3) Work Motivation influences employee performance.